THE BIOTECHNOLOGY FOR YOUNG LEARNER: EMPOWERING GIFTED CHILDREN TO BRING ACCESS TO SCIENCE KNOWLEDGE IN INCLUSIVE CLASSROOMS IN INDONESIA (Proceedings of International Conference on Special Education, 2015)
This paper presents an approach to inclusive pedagogy that enable gifted children and high performing students to bring science knowledge in inclusive classrooms of peers with diverse needs. Biotechnology for Young Learner is a program developed for gifted and more able students to learn and give tutorials of some specific themes of biotechnology to their diverse peers including children with special needs such as learning difficulties, slow learners and intellectual disabilities. Gifted and high performing children from three inclusive primary schools in Yogyakarta, Indonesia, have been involved in this program for two years. Classroom teachers provide the student tutors with series of trainings before they deliver tutorial sessions for their peers. We drew qualitative data gathered from observations, teachers’ interview, teachers’ reflections, children’s journals, and photos. We examined the impacts on the student tutors behavior, classrooms’ knowledge development, students’ attitude towards learning science, sharing and contributing skills, and social interactions. It is observed that the program has supported student tutors to develop characteristics of expert learners. We also have identified barriers of maximizing participation and engagement of all children. False conceptualizations of inclusion of classroom teachers were the main barriers presented. The paper concludes by highlighting the need for schools to establish cultures that challenge the way teachers conceptualize difference, differential learning and academic achievement. Teacher should be encouraged to work towards a pedagogy focusing on social justice and equity, viewing classroom as community of learners, enabling classroom members to contribute, rather than individuals with deficits to be fixed